Determinant Factors of Hypertension in Housewives in Ciamis Regency - Zahrani, Meisya Maudy; Saliha Puspita Prameswari, Fajria; F. Syihab, Syifa; Dewi Rahayu Fitrianingsih, Asti (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2025)
blood pressure rises above the defined normal range. Although hypertension is commonly experienced by the elderly, it can also affect adults, including housewives. Several risk factors for hypertension among housewives include age, menopausal status, use of contraceptives, dietary patterns, nutritional status, physical activity, and others. The aim of this study is to analyze the determinant factors of hypertension among housewives. Method: The cross-sectional study approach was used in the research design. The location of Ciamis Regency was chosen because it has the highest cases of hypertension in West Java based on the Kemenkes in 2018. Proportionate stratified sampling was the method employed for sampling with a total of 81 subjects in this study. Chi-square test was employed as the bivariate analysis. Result: The results show that there is a relationship between the variables nutritional status BMI (p-value = 0.016), abdominal circumference (p-value = 0.014), fat intake (p-value = 0.000), sodium intake (p-value = 0.006), and physical activity (p-value = 0.040). Conclusion: The incidence of hypertension in housewives is correlated with BMI, nutritional status, belly circumference, fat and sodium intake, and physical activity